The Role Of Financial Literacy As One Of The Influences Of Financial Behavior - Aprih Santoso; Eka Puspita Sari (Jurnal Manajemen, 2022)
This study aims to examine the impact of financial literacy and financial attitudes on financial behaviour with the locus of control as a mediation. This study uses primary data and secondary data and uses the purposive sampling method in taking the sample, as many as 89 Postgraduate Students of the Management Study Program, University of Semarang. Data analysis using PLS (Partial Least Square). This study resulted: in financial literacy and financial attitudes having a positive and significant impact on financial behaviour and locus of control is proven as a mediating variable between the influence of financial literacy and financial attitudes on financial behavior.